2022
DOI: 10.1111/jfb.15000
|View full text |Cite
|
Sign up to set email alerts
|

The potential of historical ecology to aid understanding of human–ocean interactions throughout the Anthropocene

Abstract: Marine historical ecology emerged in the scholarly literature with the aim of understanding long-term dynamics in marine ecosystems and the outcomes of past human-ocean interactions. The use of historical sources, which differ in temporal scale and resolution to most scientific monitoring data, present both opportunities and challenges for informing our understanding of past marine ecosystems and the ways in which human communities made use of them. With an emphasis upon marine social-ecological changes over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 136 publications
0
16
0
Order By: Relevance
“…In summary, we have analysed new—neglected—time series data for a charismatic, commercially important, highly migratory top predator in the Mediterranean Sea. Our study adds to a growing literature which highlights the value of historical reports and archives for generating new insights into marine ecological dynamics (Caswell et al, 2020; Engelhard et al, 2016; Schwerdtner Máñez et al, 2014; Thurstan, 2022). Here we have shown that such sources provide information not only about the target species of fisheries but also bycatch species.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In summary, we have analysed new—neglected—time series data for a charismatic, commercially important, highly migratory top predator in the Mediterranean Sea. Our study adds to a growing literature which highlights the value of historical reports and archives for generating new insights into marine ecological dynamics (Caswell et al, 2020; Engelhard et al, 2016; Schwerdtner Máñez et al, 2014; Thurstan, 2022). Here we have shown that such sources provide information not only about the target species of fisheries but also bycatch species.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, the impacts of human activities and other ecological processes that occur in the sea at longer time scales, manifested as either trends, cycles, or threshold‐like regime shifts, are not evident from most available short time series. Estimates of biomass and distribution of marine life, and how it has fluctuated over time based on recent, short time series, can therefore provide a limited perception of the status of populations and ecosystems (Caswell et al, 2020; MacKenzie & Ojaveer, 2018; Pauly, 1995; Thurstan, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As scientists try to estimate the extent of the impact climate change is having on oceans, rivers and lakes, it is important to understand that human‐induced change has also historical roots that go back centuries and that it is crucial to research in the past of this tight relationship to facilitate recovery to a “healthier” state in the future. Thurstan (2022) leads us into a journey that explores the last 200 years of human exploitation of the oceans and its impact on marine ecosystem dynamics. This contribution highlights the importance of considering past human contributions to conservation and management practices.…”
mentioning
confidence: 99%